Procesos de implantación lingüística: a planificación terminolóxica en Galicia - Galanes Santos, Iolanda (Madrygal. Revista de Estudios Gallegos, 2005)
This work aims at considering the importance of terminology in the linguistic planning of Galician language. This analyse will use the study of the recently approved General Plan of Galician Language Normalization (Plan xeral de normalización da lingua galega - PXNLG) in order to analyse the transversal sector or to improve the corpus with a focus on its implication and development for the vertical sectors. The study is based on the terminology management model by Auger and applied by Cabré and researches on the methods planned to fulfill the 8 essential activities for terminology improvement which is the Plan purpose